Adapting the Family Management Styles Framework (FMSF) for Families Caring for Older Adults with Dementia - Beeber, Anna Song (2012)
This paper presents an adaptation of the Family Management Style Framework (FMSF) -a well-established framework of family response to chronic condition care of children-- to families caring for older adults with dementia. Using the FMSF to better understand how families manage dementia care can provide clinicians with insights on how to work effectively with families. Using data from interviews with eight female caregivers of older adults with dementia this secondary analysis adapts the FMSF, and identifies new dimensions that apply specifically to families caring for older adults with dementia. The discussion draws comparisons between the family management of a child with chronic condition to management of an older adult with dementia. The paper concludes with a discussion of how understanding how families manage care of an older adult with dementia informs assessment for management styles and the tailoring of interventions specific to family, caregiver, and older adult needs.